Therapy professionals in critical care: A UK wide workforce survey. (February 2023) - Twose, Paul; Terblanche, Ella; Jones, Una; Bruce, James; Firshman, Penelope; Highfield, Julie; Jones, Gemma; Merriweather, Judith; Newey, Vicky; Newman, Helen; Rock, Claire; Wallace, Sarah
Introduction: National guidelines suggest recommended staffing levels for therapies. The aim of this study was to capture information on existing staffing levels, roles and responsibilities and service structures. Methods: An observational study using online surveys distributed to 245 critical care units across the United Kingdom (UK). Surveys consisted of a generic and five profession specific surveys. Results: Eight hundred sixty-two responses were received from 197 critical care units across the UK. Of those that responded, over 96% of units had input from dietetics, physiotherapy and SLT. Whereas only 59.1% and 48.1% had an OT or psychology service respectively. Units with ring fenced services had improved therapist to patient ratios. Discussion: There is significant variation in access to therapists for patients admitted to critical care in the UK, with many services not having services for core therapies such as psychology and OT. Where services do exist, they fall below the recommended guidance.